MicroRNAs Regulation in Osteogenic Differentiation of Mesenchymal Stem Cells - Han, Xiao; Fan, Zhipeng (Frontiers in Dental Medicine, 2021)
Mesenchymal stem cells (MSCs) are a kind of pluripotent stem cell with the potential of self-renewal and multidirectional differentiation. They can be obtained from a variety of tissues and can differentiate into a variety of cell types under different induction conditions, including osteoblasts. Because of this osteogenic property, MSCs have attracted much attention in the treatment of bone metabolism-related diseases. MicroRNAs (miRNAs), as an epigenetic factor, are thought to play an important regulatory role in the process of osteogenic differentiation of MSCs. In recent years, increasingly evidence shows that miRNAs imbalance is involved in the regulation of osteoporosis and fracture. In this review, miRNAs involved in osteogenic differentiation and their mechanisms for regulating the expression of target genes are reviewed. In addition, we also discuss the potential clinical applications and possible directions of this field in the future.